The Guitarist’s Actions in Sonant, by Mauricio Kagel (Dramaturgies, 2019)
This article analyzes the role of the performer-instrumentalist inside the instrumental theater created by composer Mauricio Kagel, taking as subject the action of the guitarist in one of his first pieces in the genre, Sonant (1960). Written for four instrumentalists, this work is based on the theatricalisation of the concert situation itself, departing from a score that combines proper sound material (partly registered in traditional notation, and partly in ”” at that time innovative ”” notation forms, such as graphic notation and verbal description of actions) with the proposition of scenic situations. These scenic situations do not start from the idea of theatrical representation, but from a situationist theatricality. Thus, the diverse actions that are proposed to the guitarist demand not only an improved and expanded instrumental technique, with the use of several resources recently explored in the instrument, but also the integration of other sound sources, scenic actions and collective reactions to the given stimuli. The resulting musical-theatrical form introduces not only the innovation of rooted traditions, but also the possibility of an aesthetic that deals with the foreseen and the unforeseen, bringing forward the artistic contribution of the performers in the very formal construction of the work, giving to gesture a musical role and proposing, finally, a reflection on the artistic practice itself.